Optimization of rc frames with reliability concepts - Alfredo Soeiro (1991)
Analysis and design optimization are considered simultaneously for reinforced concrete frames. Global displacements were considered as design variables. The nonlinear behavior of the elements was evaluated as a function of the actual stress-strain diagrams of the materials. Formation of rotational hinges with strain hardening were allowed. The acceptability of the design was guaranteed by imposing flexural reliability indices for the members, maximum global displacements for the structure and a maximum system probability of failure.